다관절 복합이동 해저로봇을 위한 탄소섬유 복합소재 프레임의 구조 해석 - 유승열(Seong-Yeol Yoo); 전봉환(Bong-Huan Jun); 심형원(Hyungwon Shim); 이판묵(Pan-Mook Lee) (Han-guk haeyang gonghak hoeji (Online), 2013)
This paper describes a finite element analysis (FEA) of the body frame of a subsea robot, Crabster200 (CR200). CR200 has six legs for mobility instead of screw type propellers, which distinguishes it from previous underwater robots such as remotely operated vehicles (ROVs) and autonomous underwater vehicles (AUVs). Another distinguishing characteristic is the body frame, which is made of carbon fiber reinforced plastic (CFRP). This body frame is designed as a rib cage structure in order to disperse the applied external loads and reduce the weight. The frame should be strong enough to support many devices for exploration and operation underwater. For a reasonable FEA, we carried out specimen tests. Using the obtained material properties, we performed a modal analysis and FEA for CR200 with a ready posture. Finally, this paper presents the FEA results for the CFRP body frame and the compares the characteristics of CFRP with conventional material, aluminum.